2022
DOI: 10.1136/bmjdrc-2021-002580
|View full text |Cite
|
Sign up to set email alerts
|

FreeStyle Libre Flash Glucose Monitoring system for people with type 1 diabetes in the UK: a budget impact analysis

Abstract: IntroductionThis study aims to estimate the budget impact of increased uptake of the FreeStyle Libre Flash Glucose Monitoring system in people with type 1 diabetes mellitus (T1DM) in the UK.Research design and methodsA budget impact model was developed, applying real-world data collected in the Association of British Clinical Diabetologists (ABCD) FreeStyle Libre Nationwide Audit. Costs of diabetes glucose monitoring in a T1DM population (n=1790) using self-monitoring of blood glucose (SMBG) or the FreeStyle L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Another limitation of the economic evaluation was the need to incorporate hypoglycaemia data from sources other than the trial, so we made the conservative assumption that isCGM had no effect on SHE rates 18 . Event rates of non‐severe and nocturnal hypoglycaemic events were taken from the IMPACT trial because this trial provided a measure of relative occurrence between isCGM and SMBG in type 1 diabetes, although the cohort had better controlled disease than our cohort 19…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another limitation of the economic evaluation was the need to incorporate hypoglycaemia data from sources other than the trial, so we made the conservative assumption that isCGM had no effect on SHE rates 18 . Event rates of non‐severe and nocturnal hypoglycaemic events were taken from the IMPACT trial because this trial provided a measure of relative occurrence between isCGM and SMBG in type 1 diabetes, although the cohort had better controlled disease than our cohort 19…”
Section: Discussionmentioning
confidence: 99%
“…It is important for policymakers and payers to have clinical and cost information when making reimbursement decisions. A budget impact analysis from a UK nationwide audit of people with type 1 diabetes suggested that isCGM is £168 per person per year more expensive to provide or purchase than SMBG, 18 with a small cost avoided (£21) due to changes in HbA1c. This provides some real‐world estimates of the budget impact of isCGM in the short‐term but does not allow policymakers and payers to understand the additional costs of isCGM in the context of longer term benefits, and does not focus on people with type 1 diabetes with high HbA1c.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations